OP1 Coronary artery disease and atherosclerotic plaque subtypes in patients with suspected angina and a coronary calcium score of zero. (7th September 2020) - Osborne-Grinter, Maia; Kwiecinski, Jacek; Doris, Mhairi; McElhinney, Priscilla; Cadet, Sebastien; Adamson, Philip D; Moss, Alastair J; Alam, Shirjel; Hunter, Amanda; Shah, Anoop SV; Mills, Nicholas L; Pawade, Tania; et al.
Abstract : Introduction: This post-hoc analysis of the SCOT-HEART (Scottish COmputed Tomography of the HEART Trial) assessed the frequency and implications of coronary artery disease (CAD) in patients with a zero coronary artery calcium score (CACS). Methods: Agatston CACS was assessed on non-contrast and CAD on contrast CT coronary angiography. Adverse plaque characteristics (APC) were visually identified as positive remodelling or low attenuation plaque and quantitative plaque burden was measured. Results: Of 642 patients with zero CACS, CAD was present in 105 (16%). Compared to patients with normal coronary arteries, those with zero CACS and CAD were older (55±9 vs 53±10 years, p=0.016) and had higher cardiovascular risk scores (14±9 vs 12±8, p=0.013). On CTCA 92 (14%) had non-obstructive CAD, 13 (2%) obstructive CAD, 14 (2%) APC and 85 (13%) low attenuation plaque burden >4%. Compared to patients with normal coronary arteries, those with zero CACS and CAD were more likely to receive statins (67% vs 17%, p<0.001), antiplatelet therapy (74% vs 28%, p<0.001), angiography (18% vs 2%, p<0.001) and revascularisation (7% vs 0%, p<0.001). Quality-of-life and symptoms were similar in patients with normal coronary arteries and those with zero CACS and CAD (p>0.05). Over 5 years of follow-up, 1 event (1%, myocardial infarction) occurred in patients with zero CACS and CAD compared to 3 events (1%, 2 myocardial infarction and 1 coronary heart disease death) in patients with normal coronary arteries. Conclusion: CAD occurs in 16% of patients with zero CACS, with prognostically significant plaque subtypes occurring in some patients, although the overall event-rate is low.